UNIVERSITY STUDENTS’ PERCEPTION OF THE EFFECTS OF CLIMATE CHANGE ON FOOD SECURITY 2023 - Jurado Falconí , Eulalia (2024)
Analyze the perception of university students regarding the effect of climate change on food security. In a National University and in a private University of Metropolitan Lima in 2023. A survey was applied to a sample of 308 students, awareness workshops were held. In Metropolitan Lima the population continues to grow, while agricultural production stagnates and land for cultivation is reduced, the poverty rate is growing, real per capita income affecting the accessibility of food. Students’ perception of climate change is influenced by the quality of the education they receive. 41% believe that they do not have sufficient knowledge, 70% maintain that in their home there is a tendency to acquire less and less food due to its limited supply in the markets and 74% think that it is because the family income They are getting smaller. Climate change education not only provides knowledge, but also empowers students to be informed and active citizens who can contribute to building a more sustainable future. It is expected that students, by understanding the impacts of climate change, can make more conscious decisions in their daily lives and contribute to collective efforts to address the problem, for this it is necessary to develop an action plan to foster a sense of individual responsibility and collective in the students with the multiplier effect in their homes. KEYWORDS: Food security, availability, accessibility, food crisis, climate change, hunger.